Effectiveness and Safety of Knee Joint Arthroscopy for Treating Meniscus Tears - Sherkulovich, Rakhmanov Shakhimordon (American Journal of Bioscience and Clinical Integrity, 2024)
This study examines the effectiveness and safety of knee joint arthroscopy in treating meniscus tears. A retrospective analysis was conducted on 150 patients aged 18 to 65 years who underwent arthroscopic surgery for meniscus injuries. The study found significant postoperative improvements in pain reduction and joint mobility. Preoperative pain levels averaged 8.2 on the visual analog scale (VAS), which decreased to 2.1 post-surgery, with over 90% of patients reporting reduced pain. Range of motion improved from 60 degrees preoperatively to 120 degrees postoperatively. The average recovery time was 12 weeks, with faster recovery observed in patients adhering to rehabilitation protocols. Complications occurred in less than 5% of the patients and were successfully managed. This study highlights the minimally invasive nature of arthroscopy, its quick recovery times, and its safety profile, making it an effective treatment option for meniscus tears. Further research on long-term outcomes and personalized rehabilitation protocols is recommended.